2019
DOI: 10.1155/2019/1568720
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness ofOpuntia ficus indicaL.inermisSeed Oil in the Protection and the Healing of Experimentally Induced Gastric Mucosa Ulcer

Abstract: Gastric ulcer is a painful lesion of the gastric mucosa which can be disabling, or even more very serious in the case of a perforation of the stomach and internal hemorrhage. Traditional pharmacopeias have shown the efficacy of various plant extracts in the treatment of this pathology. Some extracts from Opuntia ficus indica (OFI) have been proven to have medicinal therapeutic benefits. The aim of this study was to investigate the preventive and curative effects of OFI seed oil extracted by cold pressing on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 73 publications
2
28
4
Order By: Relevance
“…From these studies, it can be concluded that the oil of O. ficus-indica seeds is not toxic even at high doses. Khémiri et al (2019) evaluated the O. ficus-indica seeds oil’s acute toxicity in adult rats, revealing that the oil did not display any signs of toxicity or death in orally administered animals with either a 3.5 mL dose or a 7 mL oil/kg dose over the five days of the study period [ 24 ]. In this study, we also intended to examine the possible mechanism of action for ODSO’s antihyperglycemic effect [ 7 ], by evaluating this oil’s effect on the glucose absorption ability of the isolated rat hemidiaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…From these studies, it can be concluded that the oil of O. ficus-indica seeds is not toxic even at high doses. Khémiri et al (2019) evaluated the O. ficus-indica seeds oil’s acute toxicity in adult rats, revealing that the oil did not display any signs of toxicity or death in orally administered animals with either a 3.5 mL dose or a 7 mL oil/kg dose over the five days of the study period [ 24 ]. In this study, we also intended to examine the possible mechanism of action for ODSO’s antihyperglycemic effect [ 7 ], by evaluating this oil’s effect on the glucose absorption ability of the isolated rat hemidiaphragm.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have emerged as a source of compounds with potential antiulcer activity. 50,51 Previous report by our group investigated the PSO solubilizing ability of ibuprofen in self-nanoemulsifying drug delivery system for improved solubility and as protection factor from peptic ulcer induced by the enhanced solubility of ibuprofen. 52 These promising results were taken a step further to prove the efficacy of PSO in ulcer protection through formulation into NLCs with improved stability and efficacy characteristics when compared with the self-nanoemulsifying drug delivery system.…”
Section: Effect Of Pso and Pso-nlcs Formula On Gastric Mucosal Oxidatmentioning
confidence: 99%
“…This method does not use any chemical products during the extraction process and ensures the preservation of oil components. The extracted seed oil was then stored until use in anti-UV hermetic clean bottles as previously described [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total flavonoid content in safflower seed oil was assayed as described [ 62 ] and slightly modified [ 57 ]. 1.5 mL of 2% aluminium trichloride solution (AlCl 3 ) was added to 1.5 mL DMSO dissolved oil.…”
Section: Methodsmentioning
confidence: 99%